Thick brane in mimetic-like gravity - C.A.S. Almeida; F.C.E. Lima; S.S. Mishra; Gonzalo J. Olmo; P.K. Sahoo (Nuclear Physics B)
We analyze a five-dimensional braneworld governed by a mimetic-like gravity, a plausible candidate for explaining dark matter. Within this scenario, we examine Friedmann-Lemaître-Robertson-Walker (FLRW) branes and find that constant curvature and Minkowskian solutions are possible. We then show that the mimetic model leads to kink-like and lump-like thick brane solutions without the need for spontaneous symmetry breaking. Its stability against small perturbations is also verified.